Evaluation of potassium soil tests and methods for mapping soil fertility properties in Iowa corn and soybean fields - Barbagelata, Pedro Anibal (Iowa State University, 2020)
Tesis para obtener el grado de Philosophical Doctor (PhD), Major: Soil Science, de la Iowa State University, en 2006